Biodiversity of the aculeate wasps (Hymenoptera: Aculeata) of the Arabian Peninsula: Vespoidea, Tiphiidae - Gadallah, Neveen S.; Brothers, Denis J. (Zootaxa, 2020)
An updated checklist of the Arabian species of Tiphiidae is provided here. The list includes 38 identified valid species in 10 genera and three subfamilies: Anthoboscinae (1 genus, 2 species), Myzininae (7 genera, 29 species), and Tiphiinae (2 genera, 7 species). Distributions, both on the Peninsula and extra-limital, are provided for each species; 24 species (63%) are endemic to the Arabian Peninsula.